Ice streams in the Laurentide Ice Sheet : a new mapping inventory. - Margold, M.; Stokes, C.R.; Clark, C.D.; Kleman, J. (Journal of Maps, 2015)
Rapidly flowing ice streams dominate the drainage of continental ice sheets and are a key component of their mass balance. Due to their potential impact on sea level, their activity in the Antarctic and Greenland Ice Sheets has undergone detailed scrutiny in recent decades. However, these observations only cover a fraction of their ‘life-span’ and the subglacial processes that facilitate their rapid flow are very difficult to observe. To circumvent these problems, numerous workers have highlighted the potential of investigating palaeo-ice streams tracks, preserved in the landform and sedimentary record of former ice sheets. As such, it is becoming increasingly important to know where and when palaeo-ice streams operated. In this paper, we present a new map of ice streams in the North American Laurentide Ice Sheet (LIS; including the Innuitian Ice Sheet), which was the largest of the ephemeral Pleistocene ice sheets and where numerous ice streams have been identified. We compile previously published evidence of ice stream activity and complement it with new mapping to generate the most complete and consistent mapping inventory to date. The map depicts close to three times as many ice streams (117 in total) compared to previous inventories, and categorises them according to the evidence they left behind, with some locations more speculative than others. The map considerably refines our understanding of LIS dynamics, but there is a clear requirement for improved dating of ice stream activity.